Menemukan Ketenangan Hati di Tengah Badai Informasi: Refleksi Tauhid Rububiyah bagi Netizen : Penelitian - Dadan Nurulhaq; Miftahul Fikri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The digital era has ushered humanity into the phenomenon of information overload, which affects not only cognition but also mental health and spiritual stability. Netizens are frequently trapped in digital anxiety caused by social media algorithms, "flexing" phenomena, and the influx of hoaxes that trigger a loss of inner peace. This article aims to explore the relevance of Tawheed ar-Rububiyyah as a theological-contemplative solution to the challenges of the virtual world. Through a qualitative-descriptive approach with an Islamic Psychological perspective, this paper analyzes how absolute faith in Allah as Al-Mudabbir (The Regulator) and Ar-Razzaq (The Provider) can serve as a spiritual anchor for individuals. The reflection results indicate that strengthening Tawheed ar-Rububiyyah is capable of reducing FOMO (Fear of Missing Out) anxiety, increasing resilience against digital social pressure, and realigning a netizen's life orientation toward divine decree over the power of algorithms. In conclusion, Tawheed ar-Rububiyyah functions as essential spiritual "software" to realize mental health and tranquility of the soul (tuma’ninah) amidst today's information disruption.